Printed gas sensors - Dai, Jie; Ogbeide, Osarenkhoe; Macadam, Nasiruddin; Sun, Qian; Yu, Wenbei; Li, Yu; Su, Bao-Lian; Hasan, Tawfique; Huang, Xiao; Huang, Wei (Chemical Society reviews)
The rapid development of the Internet of Things (IoT)-enabled applications and connected automation are increasingly making sensing technologies the heart of future intelligent systems. The potential applications have wide-ranging implications, from industrial manufacturing and chemical process control to agriculture and nature conservation, and even to personal health monitoring, smart cities, and national defence. Devices that can detect trace amounts of analyte gases represent the most ubiquitous of these sensor platforms. In particular, the advent of nanostructured organic and inorganic materials has significantly transformed this field. Highly sensitive, selective, and portable sensing devices are now possible due to the large surface to volume ratios, favorable transport properties and tunable surface chemistry of the sensing materials. Here, we present a review on the recent development of printed gas sensors. We first introduce the state-of-the-art printing techniques, and then describe a variety of gas sensing materials including metal oxides, conducting polymers, carbon nanotubes and two-dimensional (2D) materials. Particular emphases are given to the working principles of the printing techniques and sensing mechanisms of the different material systems. Strategies that can improve sensor performance via materials design and device fabrication are discussed. Finally, we summarize the current challenges and present our perspectives in opportunities in the future development of printed gas sensors. This review presents the recent development of printed gas sensors based on functional inks.